Cardiomyocyte-specific Piezo1 deficiency mitigates ischemia-reperfusion injury by preserving mitochondrial homeostasis - Honglin Xu; Xin Chen; Shangfei Luo; Jintao Jiang; Xianmei Pan; Yu He; Bo Deng; Silin Liu; Rentao Wan; Liwen Lin; Qiaorui Tan; Xiaoting Chen; et al. (Redox Biology)
Ca2+ overload and mitochondrial dysfunction play crucial roles in myocardial ischemia-reperfusion (I/R) injury. Piezo1, a mechanosensitive cation channel, is essential for intracellular Ca2+ homeostasis. The objective of this research was to explore the effects of Piezo1 on mitochondrial function during myocardial I/R injury. We showed that the expression of myocardial Piezo1 was elevated in the infracted area of I/R and cardiomyocyte-specific Piezo1 deficiency (Piezo1△Myh6) mice attenuated I/R by decreasing infarct size and cardiac dysfunction. Piezo1△Myh6 regulated mitochondrial fusion and fission to improve mitochondrial function and decrease inflammation and oxidative stress in vivo and in vitro. Mechanistically, myocardial Piezo1 knockout alleviated intracellular calcium overload to normalize calpain-associated mitochondrial homeostasis. Our findings indicated that Piezo1 depletion in cardiomyocytes partially restored mitochondrial homeostasis during cardiac ischemia/reperfusion (I/R) injury. This study suggests an innovative therapeutic strategy to alleviate cardiac I/R injury.